Hubungan kebiasaan bermain game online dan konformitas teman sebaya dengan motivasi belajar peserta didik sekolah dasar se-kecamatan wonosegoro - Ichsanudin, Amin; Riyadi, Riyadi; Wahyuningsih, Siti (Didaktika Dwija Indria, 2025)
This study aims to find out whether there is a relationship between online gaming habits and peer conformity with learning motivation. The research design is quantitative with  an ex-postfacto correlational research method. The data collection technique used was a questionnaire distributed to students of the state elementary school in Wonosegoro district. The results of this study are 1) there is a significant negative relationship between the habit of playing online games and learning motivation at a "moderate" correlation level. 2) There was a significant negative relationship between peer conformity and learning motivation at the level of "strong" correlation. 3) There was a significant relationship between online gaming habits and peer conformity and simultaneous learning motivation at the level of "strong" correlation. The implication of this study is the need for time management in playing online games and self-control so that they are not influenced by peers who play online games so that learning motivation does not decrease.